Exploration of the Nurse Shark (Ginglymostoma cirratum) Plasma Immunoproteome Using High-Resolution LC-MS/MS - Bakke, Fiona K.; Gundappa, Manu Kumar; Matz, Hanover; Stead, David A.; Macqueen, Daniel J.; Dooley, Helen (Frontiers in Immunology, 2022)
Many animals of scientific importance lack species-specific reagents (e.g., monoclonal antibodies) for in-depth studies of immune proteins. Mass spectrometry (MS)-based proteomics has emerged as a useful method for monitoring changes in protein abundance and modifications in non-model species. It can be used to quantify hundreds of candidate immune molecules simultaneously without the generation of new reagents. Here, we used MS-based proteomics to identify and quantify candidate immune proteins in the plasma of the nurse shark (Ginglymostoma cirratum), a cartilaginous fish and representative of the most basal extant vertebrate lineage with an immunoglobulin-based immune system. Mass spectrometry-based LC-MS/MS was performed on the blood plasma of nurse sharks immunized with human serum albumin (n=4) or sham immunized (n=1), and sampled at days 0 (baseline control), 1, 2, 3, 5, 7, 14, 21, 28, 25, 42 and 49. An antigen-specific antibody response was experimentally confirmed post-immunization. To provide a high-quality reference to identify proteins, we assembled and annotated a multi-tissue de novo transcriptome integrating long- and short-read sequence data. This comprised 62,682 contigs containing open reading frames (ORFs) with a length >80 amino acids. Using this transcriptome, we reliably identified 626 plasma proteins which were broadly categorized into coagulation, immune, and metabolic functional groups. To assess the feasibility of performing LC-MS/MS proteomics in nurse shark in the absence of species-specific protein annotations, we compared the results to an alternative strategy, mapping peptides to proteins predicted in the genome assembly of a related species, the whale shark (Rhincodon typus). This approach reliably identified 297 proteins, indicating that useful data on the plasma proteome may be obtained in many instances despite the absence of a species-specific reference protein database. Among the plasma proteins defined against the nurse shark transcriptome, fifteen showed consistent changes in abundance across the immunized shark individuals, indicating a role in the immune response. These included alpha-2-macroglobulin (A2M) and a novel protein yet to be characterized in diverse vertebrate lineages. Overall, this study enhances genetic and protein-level resources for nurse shark research and vastly improves our understanding of the elasmobranch plasma proteome, including its remodelling following immune stimulation.